Investigation of Solar Panel Performance Based on Different Wind Velocity Using ANSYS Software - Leow Wai Zhe; Mohd. Irwan Bin Yusoff; Muhammad Irwanto Misrun; Amelia Binti Abdul Razak; Safwati Ibrahim; Nur Syafiqah Binti Zhubir (Institute of Advanced Engineering and Science, 2016)
The low conversion energy efficiency of solar panel is affected by the several environmental issues. Solar radiation, ambient temperature, dust accumulation and wind velocity are the environmental problems. This main goal of this paper is to understanding the solar panel behavior under varying of wind velocity amounts. A three-dimension (3-D) model of solar panel is conducted in the present investigation. The solar panel model is simulated under given operating condition and different amounts of wind velocity. Four different of wind velocity value of 0 m/s, 0.43 m/s, 2.5 m/s and 6.95 m/s was selected to examine the solar panel performance. The simulation results are obtained with ANSYS simulation software. The temperature distribution of the solar panel model will be discussed in this current paper. The simulation result is showed highest wind velocity can be provided good cooling effect for the solar panel model in order to enable the solar panel can be operated to perform well at lower temperature.